Study on sintering mechanism and mechanical properties of Fe–Ni elastocaloric refrigeration alloy through molecular dynamics simulation. (August 2022) - Li, Xianfa; Shi, Yongjun; Chen, Tingting; Wang, Shuyao; Fan, Kaijun
Abstract: In this paper, the embedded atom method (EAM) potential function was introduced to study the sintering mechanism and the mechanical properties of Fe14.6Ni (at%) elastocaloric refrigeration alloys through molecular dynamics (MD) simulations. The analysis of the energy field showed that sintering mechanism was atoms behaviors of vibration, diffusion and recombination when affected by different potential energy fields and kinetic energy fields. In addition, the analysis of the sintering process parameters further confirmed the sintering mechanism. The evaluation of the mechanical properties of the alloy showed that mechanical properties of the Fe14.6Ni (at%) alloy were greatly affected by the strain rate and temperature. This work provided theoretical guidance for the preparation of Fe14.6Ni (at%) elastocaloric refrigeration alloy and laid a foundation for the study of elastocaloric effects. Graphical Abstract: ga1 Highlights: The sizes greatly influence on the melting point. The mechanism of sintering involve the vibration, diffusion, and recombination of atoms. The process parameters were characterized and the results were consistent with the energy field analysis results. The experimental results of X-ray diffraction were in good agreement with the MD simulation results. The mechanical behaviors showed the super elastic effect of the Fe–Ni elastocaloric refrigeration alloy.